Relationship between neutralizing and opsonizing monoclonal antibodies against foot-and-mouth disease virus - Summerfield, Artur; Gerber, Heidi; Schmitt, Rebeka; Liniger, Matthias; Grazioli, Santina; Brocchi, Emiliana (Frontiers in Veterinary Science, 2022)
Previous studies demonstrated that polyclonal antibodies against foot-and-mouth disease virus (FMDV) generated by vaccination can mediate immune functions not only through virus neutralization but also through promoting virus uptake by macrophages and dendritic cells that are otherwise resistant to FMDV infection. This causes abortive infections resulting in activation, enhanced antigen presentation but also cell death. Here we report the use of RAW264.7 cells representing a murine macrophage cells line to characterize opsonizing functions of a collection of monoclonal antibodies (mAbs) against FMDV O and A serotypes. We demonstrate that all neutralizing immunoglobulin G isotype mAbs are able to opsonize FMDV resulting in increased cell death of RAW264.7 cells. In contrast, neutralizing IgM antibodies did not possess this activity. Opsonization was observed with broader reactivity within the serotype when compared to neutralization. Importantly, the anti-O serotype D9 mAb reacting with the continuous epitope within the G-H loop of VP1 that contains the RGD binding site of FMDV, opsonized several FMDV serotypes despite its restricted neutralizing activity within the O serotype. Furthermore, by generating RAW264.7 cells expressing bovine CD32, an easy-to-use cell-based assay system to test for bovine antibody-dependent enhanced infection of FMDV was generated and tested with a collection of sera. The data indicate that opsonizing titers correlated better with vaccine dose when compared to neutralizing titers. On the other hand, neutralization and opsonization titers were similar predictive of protection. We conclude that low avidity interactions are sufficient to mediate Fc receptor-mediated immune functions that could contribute to protective immune responses against FMDV.